Neglected aspects of motion-event description deixis, asymmetries, constructions - Sarda, Laure; Fagard, Benjamin (Human cognitive processing ;, 2022)
"The idea of this book on "Neglected Aspects of Motion Event Descriptions" comes from the observation that, over the last 30 years, much attention has been devoted to the manner/path divide in relation to the distinction between Verb-Framed and Satellite-Framed languages. This mainstream focus has left aside other aspects of motion event descriptions. The chapters of this volume take an in-depth look at three less-studied aspects of motion expression. The first part of the book focusses on directional deixis, especially in relation to associated motion and visual motion. The second part explores variations in Source-Goal asymmetries. The third part investigates different types of motion event constructions, e.g., with various types of co-events. Many languages are taken into consideration throughout the 11 chapters, which gives the volume a clear typological dimension. This book is intended for students and academics interested in motion, spatial semantics, typological variation and cognitive linguistics"--